Peningkatan Prestasi Belajar IPA Melalui Model Discovery Learning pada Siswa SD Negeri Gentan 01 Sukoharjo - Bektiningsih Bektiningsih (Journal of Biology Learning, 2020)
The aim of this research is to increase the academic achievement of science to the students of VIB SD Negeri Gentan 01 in the academic year 2019/2020 by using discovery learning method. This research was done with two cycles, and each cycle consist of plan, action, data account, and reflection. The place of research is SD Negeri Gentan 01 with the subject of the reseach is the students of class VIB consist of 23 students. The data account is done by observasion, documentation, and test. Analyzing data with three steps, they are reduction data, presentation data, and conclusion or verification. By  discovery learning method can increase the academic achievement of science from the first average value is 61.73 until the second average value become 84.13.